Genetic Divergence among On-farm Collections for Yield and Yield-related Traits in Ginger (Zingiber officinale R.) - TUMMINAKATTI, ALTAF; Fakrudin, B; Maruthiprasad, B. N.; Vishnuvardhana; Suresha, G. J.; Manjunath, G.; Venkatesha, J. (International Journal of Bio-resource and Stress Management, 2023)
The present investigation was carried out at the farmer’s field Neshwi village, Haveri District of Karnataka, India during kharif season (May, 2021 to January, 2022). The improvement of crop relies heavily on genetic diversity. The objective of the study was to assess the genetic divergence of 76 diverse genotypes of ginger collected from different parts of the Karnataka, India which including four checks. The genetic divergence of ginger genotypes was assessed using Mahalanobis D2 statistics. Genetic divergence studies revealed considerable genetic diversity among 76 genotypes of ginger for a set of ten quantitative traits pertaining to the growth and yield characters viz., height of the shoot (cm), leaf area (cm2), number of primary rhizomes, length of the primary rhizome (cm), girth of the primary rhizome (cm), number of secondary rhizomes, length of the secondary rhizome (cm), girth of the secondary rhizome (cm), crop duration (number of days) and rhizome yield plant-1 (g). Analysed 76 ginger genotypes were clustered based on similarities between their D2 values using Tocher’s method, resulting in 14 distinct groups. Considerable diversity within and between 14 clusters was observed among the genotypes. The characteristics such as average rhizome yield plant-1, girth of the primary rhizome and length of the primary rhizome were the main factors in differentiating the genotypes of ginger studied. Utilizing genotypes from clusters with high inter-cluster distances, such as clusters VI and XIII, VI and XIV and X and XIV can form potential pre-breeding material for the improvement of ginger crop.